18. ĐÁNH GIÁ HIỆU QUẢ PHÁC ĐỒ PALB Ở BỆNH NHÂN LOÉT HÀNH TÁ TRÀNG CÓ NHIỄM H.PYLORI TẠI PHÒNG KHÁM NỘI TIÊU HÓA - BỆNH VIỆN HỮU NGHỊ ĐA KHOA NGHỆ AN (Tạp chí Y học Cộng đồng, 2025)
Research objective: To evaluate the effectiveness of the PALB regimen in eradicating H. pylori in patients with duodenal ulcers infected with H. pylori and factors related to the eradication effectiveness.Research method: A series of cases was studied on 111 patients with duodenal ulcers infected with H. pylori treated with the PALB regimen from January 2024 to August 2024, at the Gastroenterology Clinic - Nghe An General Friendship Hospital. The diagnostic criteria were endoscopy with images of duodenal ulcers accompanied by a positive rapid urease test.Research results: The average age was 49.16 ± 14.50. The lowest age was 18 and the highest was 79; the female/male ratio was 1.36/1. The PALB regimen achieved an H. pylori eradication rate of 92.8%. There was no difference in the rate of H. Pylori eradication among age groups, gender and ulcer size with p > 0.05. No statistically significant correlation was found between H. Pylori eradication and factors such as gender, age, ulcer size (p > 0.05). The rate of H. Pylori eradication in the group of patients with high drug compliance was 96.2% and in the group with low drug compliance was 42.9%. There was a statistically significant correlation between H. Pylori eradication and treatment compliance (p < 0.05). The side effects were mainly mild (15.3%), transient, moderate (4.5%) and there were no severe effects.Conclusion: The effectiveness of H. Pylori eradication of the 4-drug regimen with Levofloxacin was 92.8%, with no serious side effects. High patient compliance is one of the factors determining the effectiveness of H. Pylori eradication.
Keywords: Phác đồ PALB; loét hành tá tràng; nhiễm H.Pylori; Bệnh viện Hữu nghị đa khoa Nghệ An